A kind of low alloy high wear-resistant steel and preparation method thereof
By optimizing the alloy composition and heat treatment process of low-alloy steel, a low-alloy high-wear resistant steel was designed, with structural characteristics of 20% ferrite + 80% martensite. Normalization and two-phase zone critical annealing process were adopted to solve the problem that existing domestic wear-resistant steels were difficult to improve wear resistance and maintain strength and toughness at the same time, and achieved better wear resistance and strength and toughness matching.
Patent Information
- Application Number
- CN202410188646.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-02-20
AI Technical Summary
While improving wear resistance, existing domestic wear-resistant steels are difficult to maintain good strength and toughness, and there is a gap in performance stability compared with foreign products.
By optimizing the alloy composition and heat treatment process of low-alloy steel, a low-alloy high-wear resistant steel was designed, with chemical compositions including C 0.1-0.3%, Mn 1.1-1.8%, Si 0.4-0.6%, etc. The volume percentages of ferrite and martensite in the structure are 20% and 80%, and the process flow of normalizing and critical annealing in the two-phase zone is adopted.
The high wear resistance and good strength and toughness matching of low alloy high wear steel is achieved, surpassing the performance of commercial single-phase martensite wear resistance steel and typical DP980 duplex steel.
Smart Images

Figure CN118086770B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a low-alloy high-wear-resistant steel and a preparation method thereof. Background Art
[0002] At present, the supply of domestic wear-resistant steel is mainly concentrated in low-end products of HB360 and HB400 levels. Wear-resistant steel above HB400 still mainly relies on imports. Compared with imported wear-resistant steel plates, domestic wear-resistant steel plates have higher hardness but average toughness and plasticity. The performance stability and overall quality of the products are still far behind those of foreign products. Low alloy steel is widely used in industrial manufacturing due to its high hardness, good comprehensive mechanical properties, welding performance, relatively simple manufacturing process and low processing cost. By appropriately adjusting the type and content of alloy elements and optimizing the heat treatment process, it is expected to increase the hardness of alloy steel while retaining good toughness and improving its wear resistance. Therefore, it is of great research significance and industrial application value to explore the mechanism of action of low alloy steel composition and heat treatment process on its mechanical properties and wear resistance, so as to design low alloy steel with high wear resistance and excellent comprehensive performance.
[0003] Therefore, how to optimize the alloy composition and heat treatment process to improve the wear resistance of the material while maintaining a good match between its mechanical properties and strength is a problem that technical personnel in this field currently need to solve. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a low-alloy high-wear-resistant steel and a preparation method thereof, and to optimize the alloy composition of the low-alloy high-wear-resistant steel so that it has better wear resistance, thereby effectively solving the problems of simultaneously improving wear resistance and maintaining good strength and toughness in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a low-alloy high wear-resistant steel is provided, comprising the following chemical components in weight percentage: C 0.1-0.3%, Mn 1.1-1.8%, Si 0.4-0.6%, Cr0.1-0.4%, Ni 0.1-0.3%, Cu 0.1-0.4%, Al 0.01-0.03%, Mo 0.1-0.3% and V0.1-0.3%, and the balance is Fe.
[0006] Furthermore, the low alloy high wear resistant steel comprises the following chemical components in weight percentage: C 0.2%, Mn 1.2%, Si 0.5%, Cr 0.2%, Ni 0.2%, Cu 0.2%, Al 0.02%, Mo 0.2% and V 0.2%, with the balance being Fe.
[0007] Furthermore, the volume percentage of each phase in the low alloy high wear resistant steel structure is: ferrite 15-25% and martensite 75-85%.
[0008] Furthermore, the volume percentage of each phase in the low alloy high wear resistant steel structure is: ferrite 20% and martensite 80%.
[0009] In the low-alloy high wear-resistant steel of the present invention, the carbon element is an important factor that directly determines the hardness and hardenability of the material in the low-alloy wear-resistant steel. With the increase of carbon content, the content of carbides with high hardness in the organization increases and the supersaturation of carbon in martensite increases, which will significantly improve the hardness and strength of the matrix. However, when the carbon content is too high, it will reduce the toughness and plasticity of the material and increase its brittleness, which is not conducive to the improvement of wear resistance, and its welding performance is greatly reduced. The carbon content will significantly affect the morphology and properties of the martensitic structure. In low-carbon steel, martensite basically exists in the form of laths and has a good toughness-plasticity match; but in high-carbon steel, the content of lamellar martensite increases, resulting in a significant increase in the matrix hardness but a decrease in toughness. Therefore, it is necessary to comprehensively consider controlling the C content to 0.1-0.3wt%.
[0010] Manganese can strongly improve the strength and hardenability of steel. Manganese is dissolved in ferrite and austenite, plays the role of expanding the austenite phase region, and raises the critical temperature. Manganese can also greatly reduce the martensitic transformation temperature of steel and the critical cooling rate during quenching to improve its hardenability. Studies have shown that appropriate manganese content can not only improve the strength and hardness of steel, but also improve the toughness and hardenability of steel. However, when the manganese content is too high, the impact toughness of steel begins to decline, which also has an adverse effect on its hardenability and welding performance. Therefore, the content of Mn is controlled to be 1.1-1.8wt% by comprehensive consideration.
[0011] The addition of silicon can hinder the nucleation and growth of carbides and improve the stability of austenite, which can improve the hardenability and tempering stability of steel. However, when the silicon content is too high, although it can further improve the hardness of the alloy steel, it has an extremely adverse effect on toughness. Therefore, the Si content is controlled to 0.4-0.6wt% after comprehensive consideration.
[0012] The use of chromium in combination with manganese and silicon can further improve the hardenability of steel. The solid solution of chromium in austenite will inhibit the decomposition of martensite, making it easier to obtain lath martensite structure during annealing. The impact toughness of steel will first increase and then decrease with the increase of chromium content. In addition, chromium is easy to form carbon compounds, thereby improving wear resistance. Therefore, the Cr content is controlled to be 0.1-0.4wt% after comprehensive consideration.
[0013] Molybdenum is mainly present in steel in the form of solid solution, which plays a role in solid solution strengthening and can effectively increase the hardenability of steel. In addition, adding molybdenum and nickel at the same time can significantly improve precipitation strengthening and fine grain strengthening, and improve the hardness of the matrix. Therefore, considering comprehensively, the content of Mo is controlled to be 0.1-0.3wt%.
[0014] Nickel has a similar effect to silicon, which can inhibit the precipitation of carbides and improve the stability of austenite. However, nickel is a relatively scarce resource, and the addition of nickel is not conducive to reducing costs. Therefore, the content of Ni is controlled to 0.1-0.3wt% after comprehensive consideration.
[0015] Vanadium has a strong affinity with C and can precipitate fine carbonitrides, which play a role in grain refinement and thus improve the strength and toughness of steel. However, because the formation of carbides reduces the carbon content in austenite, resulting in a lower volume fraction of austenite at the same heating temperature, a higher temperature is required to obtain the same martensite volume fraction compared to steel without Nb and V elements. Therefore, considering all factors, the V content is controlled to be 0.1-0.3wt%.
[0016] Copper can improve the corrosion resistance of steel. At the same time, adding appropriate copper can refine the grains and form copper precipitates to improve the strength and toughness of steel. However, when the content is high, it is not conducive to hot deformation processing, and copper brittleness occurs during hot deformation processing. Therefore, the Cu content is controlled to 0.1-0.4wt% after comprehensive consideration.
[0017] The present invention also provides a method for preparing the above-mentioned low-alloy high-wear-resistant steel, which comprises the following steps in sequence:
[0018] (1) Smelting and forging raw materials according to chemical composition, and then hot rolling the billets into thin steel plates with a thickness of 2 mm;
[0019] (2) Normalizing: Heat the steel to above Ac3 temperature, keep it warm for 5-15 minutes, and then air cool it to room temperature;
[0020] (3) Two-phase critical annealing: Heat the cooled steel to the two-phase critical annealing temperature of 800-850℃, keep it warm for 1 hour, and quench it to obtain low-alloy high-wear-resistant steel.
[0021] Furthermore, in step (2), the Ac3 temperature is 721°C.
[0022] Furthermore, in step (2), the normalizing temperature is 900°C and the acceleration rate is 20°C / s.
[0023] Furthermore, in step (2), the air cooling rate is 20°C / s.
[0024] Furthermore, in step (3), the critical annealing temperature of the two-phase region is 825°C.
[0025] Furthermore, in step (3), water quenching is used for quenching.
[0026] During preparation, due to the short holding time of normalizing, the phase transformation can be controlled at the initial stage of complete austenitization, avoiding too long heating time, continuous growth of austenite grains, resulting in coarse martensite structure after quenching, and causing a decrease in the mechanical properties of the alloy steel. Then air-cool to room temperature at a rate of 20℃ / s, and obtain a two-phase structure of ferrite and pearlite at a slower cooling rate. After that, it is heated again to the critical annealing of the two-phase region, and the austenite will nucleate and grow along the interface between ferrite and carbide, and then water quenching is carried out, and the austenite is completely transformed into martensite at a faster cooling rate, while the ferrite is retained to room temperature.
[0027] The volume fractions of each phase in the low alloy high wear resistant steel structure prepared by the above method are: 20% ferrite and 80% martensite. The soft phase ferrite can adapt to plastic deformation and absorb energy during friction and wear, and can inhibit the initiation and expansion of cracks during wear to a certain extent, thereby improving its service life.
[0028] The present invention has the following beneficial effects:
[0029] 1. The microstructure characteristics of the obtained low alloy high wear-resistant steel are ferrite (20%) + martensite (80%). The optimized dual phase (DP) wear-resistant steel has better wear resistance than commercial single phase martensitic wear-resistant steel (NM400) and commercial typical DP980 dual phase steel (C 0.2%, Mn 2%, Si 1.6%) of different microstructure steel grades (AIQ, FIQ, MIQ, TFM), and at the same time its mechanical properties maintain better strength and toughness matching. AIQ is a dual phase steel with austenitization first, then intercritical annealing, and then quenching to obtain finer martensitic islands; FIQ is a dual phase steel with the starting structure ferrite (Ferrite) / pearlite (Pearlite) heated to the intercritical annealing, and then quenching to obtain coarser martensitic islands; MIQ is a dual phase steel with the starting structure martensite (Martensite) heated to the intercritical annealing, and then quenching to obtain coarser martensitic islands. The steel is a dual-phase steel with fibrous martensite islands obtained by annealing and subsequent quenching; TFM is a tempered full martensite steel. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1This is a schematic diagram of the preparation process of the present invention;
[0031] Figure 2 This is the microstructure diagram of the low alloy high wear-resistant steel obtained in Example 2. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] A low alloy high wear-resistant steel comprises the following chemical components in weight percentage: C 0.1%, Mn 1.1%, Si 0.4%, Cr 0.1%, Ni 0.1%, Cu 0.1%, Al 0.01%, Mo 0.1% and V 0.1%, and the balance is Fe.
[0035] The method for preparing the above-mentioned low alloy high wear-resistant steel comprises the following steps in sequence:
[0036] (1) Smelting and forging raw materials according to chemical composition, and then hot rolling the billets into thin steel plates with a thickness of 2 mm;
[0037] (2) Normalizing: Heat the steel to 900℃ for normalizing at an acceleration rate of 20℃ / s, keep warm for 5 minutes, and then air cool to room temperature at an air cooling rate of 20℃ / s;
[0038] (3) Two-phase critical annealing: The cooled steel is heated to the two-phase critical annealing temperature of 825°C, kept at this temperature for 1 hour, and water quenched to obtain low alloy high wear-resistant steel.
[0039] Example 2
[0040] A low alloy high wear-resistant steel comprises the following chemical components in weight percentage: C 0.2%, Mn 1.2%, Si 0.5%, Cr 0.2%, Ni 0.2%, Cu 0.2%, Al 0.02%, Mo 0.2% and V 0.2%, and the balance is Fe.
[0041] The method for preparing the above-mentioned low alloy high wear-resistant steel comprises the following steps in sequence (such as Figure 1 shown):
[0042] (1) Smelting and forging raw materials according to chemical composition, and then hot rolling the billets into thin steel plates with a thickness of 2 mm;
[0043] (2) Normalizing: Heat the steel to 900℃ for normalizing at an acceleration rate of 20℃ / s, keep warm for 10min, and then air cool to room temperature at an air cooling rate of 20℃ / s;
[0044] (3) Two-phase critical annealing: The cooled steel is heated to the two-phase critical annealing temperature of 825°C, kept at this temperature for 1 hour, and water quenched to obtain a low alloy high wear-resistant steel. The microstructure diagram is shown in the figure below. Figure 2 shown.
[0045] Example 3
[0046] A low alloy high wear-resistant steel comprises the following chemical components in weight percentage: C 0.3%, Mn 1.3%, Si 0.6%, Cr 0.3%, Ni 0.3%, Cu 0.3%, Al 0.03%, Mo 0.3% and V 0.3%, and the balance is Fe.
[0047] The method for preparing the above-mentioned low alloy high wear-resistant steel comprises the following steps in sequence:
[0048] (1) Smelting and forging raw materials according to chemical composition, and then hot rolling the billets into thin steel plates with a thickness of 2 mm;
[0049] (2) Normalizing: Heat the steel to 900℃ for normalizing at an acceleration rate of 20℃ / s, keep warm for 15min, and then air cool to room temperature at an air cooling rate of 20℃ / s;
[0050] (3) Two-phase critical annealing: The cooled steel is heated to the two-phase critical annealing temperature of 825°C, kept at this temperature for 1 hour, and water quenched to obtain low alloy high wear-resistant steel.
[0051] Comparative Example 1
[0052] A ferrite-martensite dual-phase steel, the specific preparation process steps are:
[0053] (1) Obtaining slab
[0054] Its chemical composition is: C 0.2wt%, Si 1.6wt%, Mn 2wt%, and the balance is Fe and inevitable impurities.
[0055] (2) Austenitization
[0056] The steel is heated to above Ac3 and kept warm for 20 minutes. At the same time, the environment is evacuated and argon gas is introduced, with the vacuum degree being 1000Pa.
[0057] (3) Two-phase critical annealing
[0058] The austenitized steel was cooled to the critical annealing temperature of 760°C in the two-phase region at a cooling rate of 22°C / min and kept at this temperature for 1 hour.
[0059] (4) Quenching
[0060] The steel material treated in step (3) is water quenched.
[0061] Comparative Example 2
[0062] Ferrite-martensite dual-phase steel AIQ-750℃ steel, the specific preparation process steps are:
[0063] (1) Obtaining slab
[0064] Its chemical composition is: C 0.22wt%, Si 0.25wt%, Mn 1.2wt%, Cr 0.2wt%, and the balance is Fe and inevitable impurities.
[0065] (2) Austenitization
[0066] Heat the steel to above Ac3 (about 900℃) and keep it warm for 10 minutes.
[0067] (3) Two-phase critical annealing
[0068] The austenitized steel is cooled to the critical annealing temperature of the two-phase region, 750°C, and kept at this temperature for 1 hour.
[0069] (4) Quenching
[0070] Use water quenching.
[0071] Comparative Example 3
[0072] Ferrite-martensite dual-phase steel AIQ-725℃, the specific preparation process steps are:
[0073] In step (3) of this comparative example, the critical annealing temperature of the two-phase region is 725° C., and the other conditions are the same as those of comparative example 2.
[0074] Comparative Example 4
[0075] Ferrite-martensite dual-phase steel FIQ-800℃, the specific preparation process steps are:
[0076] (1) Obtaining slab
[0077] Its chemical composition is: C 0.22wt%, Si 0.25wt%, Mn 1.2wt%, Cr 0.2wt%, and the balance is Fe and inevitable impurities.
[0078] (2) Two-phase critical annealing
[0079] Heat the steel to the two-phase critical annealing temperature of 800°C and keep it at that temperature for 1 hour.
[0080] (3) Quenching
[0081] Use water quenching.
[0082] Comparative Example 5
[0083] Ferrite-martensite dual-phase steel FIQ-775℃, the specific preparation process steps are:
[0084] In step (2) of this comparative example, the critical annealing temperature of the two-phase region is 775° C., and the other conditions are the same as those of comparative example 4.
[0085] Comparative Example 6
[0086] Ferrite-martensite dual-phase steel MIQ-800℃, the specific preparation process steps are:
[0087] (1) Obtaining slab
[0088] Its chemical composition is: C 0.22wt%, Si 0.25wt%, Mn 1.2wt%, Cr 0.2wt%, and the balance is Fe and inevitable impurities.
[0089] (2) Austenitization
[0090] Heat the steel to above Ac3 (about 900℃) and keep it warm for 10 minutes.
[0091] (3) Quenching
[0092] Use water quenching.
[0093] (4) Two-phase critical annealing
[0094] The steel is reheated to the two-phase critical annealing temperature of 800°C and kept at this temperature for 1 hour.
[0095] (5) Quenching
[0096] Use water quenching.
[0097] Comparative Example 7
[0098] Ferrite-martensite dual-phase steel MIQ-790℃, the specific preparation process steps are:
[0099] In step (4) of this comparative example, the critical annealing temperature of the two-phase region is 790° C., and the other conditions are the same as those of comparative example 6.
[0100] Comparative Example 8
[0101] Ferrite-martensite dual-phase steel MIQ-775℃, the specific preparation process steps are:
[0102] In step (4) of this comparative example, the critical annealing temperature of the two-phase region is 775° C., and the other conditions are the same as those of comparative example 6.
[0103] Comparative Example 9
[0104] Ferrite-martensite dual-phase steel MIQ-750℃, the specific preparation process steps are:
[0105] In step (4) of this comparative example, the critical annealing temperature of the two-phase region is 750° C., and the other conditions are the same as those of comparative example 6.
[0106] Comparative Example 10
[0107] Tempered martensitic steel TFM-500℃, the specific preparation process steps are:
[0108] (1) Obtaining slab
[0109] Its chemical composition is: C 0.22wt%, Si 0.25wt%, Mn 1.2wt%, Cr 0.2wt%, and the balance is Fe and inevitable impurities.
[0110] (2) Austenitization
[0111] Heat the steel to above Ac3 (about 900℃) and keep it warm for 10 minutes.
[0112] (3) Quenching
[0113] Use water quenching.
[0114] (4) Tempering
[0115] Heat the steel to 500℃ for tempering and keep it warm for 1h.
[0116] (5) Quenching
[0117] Use water quenching.
[0118] Comparative Example 11
[0119] Tempered martensitic steel TFM-400℃, the specific preparation process steps are:
[0120] The tempering temperature in step (4) of this comparative example is 400° C., and the other conditions are the same as those of comparative example 10.
[0121] Comparative Example 12
[0122] Tempered martensitic steel TFM-300℃, the specific preparation process steps are:
[0123] The tempering temperature in step (4) of this comparative example is 300° C., and the other conditions are the same as those of comparative example 10.
[0124] Comparative Example 13
[0125] Tempered martensitic steel TFM-200℃, the specific preparation process steps are:
[0126] The tempering temperature in step (4) of this comparative example is 200° C., and the other conditions are the same as those of comparative example 10.
[0127] Comparative Example 14
[0128] The specific preparation process steps of full martensitic steel are as follows:
[0129] (1) Obtaining slab
[0130] Its chemical composition is: C 0.22wt%, Si 0.25wt%, Mn 1.2wt%, Cr 0.2wt%, and the balance is Fe and inevitable impurities.
[0131] (2) Austenitization
[0132] Heat the steel to above Ac3 (about 900℃) and keep it warm for 10 minutes.
[0133] (3) Quenching
[0134] Use water quenching.
[0135] The performance of commercial NM400 and DP980 steels with different microstructure phases in Example 2 and Comparative Examples 1-14 was tested, and the properties obtained by the test are shown in Table 1; the specific test process is as follows:
[0136] The sliding wear test adopts the ball-plane contact method and is carried out on a high-precision reciprocating friction and wear testing machine. The wear specimens are processed into 15mm×10mm×2mm, and the specimens are ground and polished to a mirror surface (Ra 0.02μm) before the test. Si3N4 ceramic balls with a hardness of 1500HV and a diameter of 3mm are selected as the grinding pair material. All specimens and Si3N4 balls are ultrasonically cleaned and dried in alcohol for 15 minutes before the wear test to ensure that there are no contaminants on the surface of the specimens. The friction tests are carried out in atmospheric and room temperature environments, with a relative humidity of 50%-60%, a displacement amplitude of 2.5mm, normal loads of 10N and 30N, an experimental frequency of 2Hz, and a cycle of 1×10 4 After the wear test, a 3D white light interferometer (Bruker GTK-16-0295) was used to quantitatively characterize the wear spot profile and wear volume, and then the wear performance of each alloy steel was analyzed. In order to avoid the irregular shape of the two ends of the wear mark and ensure the reliability of the experimental data, the wear volume only took the 4mm length area in the middle of the wear mark, and the wear rate (wear volume per unit length) was used as the wear resistance evaluation index.
[0137] The indentation load of the hardness test was set to 200gN, and the holding time was 15s. Before the test, the sample needs to be ground and polished to obtain a flat and uniform test surface. To ensure the accuracy of the test results, 10 points are measured for each sample and the average value is taken as the final hardness value. The tensile mechanical properties experiment was carried out in accordance with the ASTM (E-8) standard, where the tensile speed was 1.5mm / min, the thickness was 2mm, and the tensile direction of the sample was parallel to the rolling direction. The total elongation was measured using an extensometer with a gauge length of 25mm, and the maximum displacement of the extensometer was taken as the total elongation, which can maximize the accuracy of the tensile data curve. In order to reduce the random error of the experiment, the tensile test was repeated three times, and the average value of the results was taken as the value of each mechanical property.
[0138] Table 1 Performance test results
[0139]
[0140] It can be seen from Table 1 that the low alloy high wear-resistant steel of the present invention has a microstructure characteristic of ferrite (20%) + martensite (80%), and has better wear resistance than commercial single-phase martensitic wear-resistant steel (NM400) and commercial typical DP980 dual-phase steel (C 0.2%, Mn2%, Si 1.6%) of different microstructure steel grades (AIQ, FIQ, MIQ, TFM), while its mechanical properties maintain better strength-toughness matching.
[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A low alloy high wear resistant steel, characterized in that: The invention comprises the following chemical compositions in weight percentage: C 0.1-0.3%, Mn 1.1-1.8%, Si 0.4-0.6%, Cr 0.1-0.4%, Ni 0.1-0.3%, Cu 0.1-0.4%, Al 0.01-0.03%, Mo 0.1-0.3% and V 0.1-0.3%, and the balance is Fe; The method for preparing the low alloy high wear resistant steel comprises the following steps in sequence: (1) Smelting and forging raw materials according to chemical composition, and then hot rolling the billets into 2 mm thick thin plates; (2) Normalizing: Heat the steel to above Ac3 temperature, keep it warm for 5-15 minutes, and then air cool it to room temperature; (3) Two-phase critical annealing: Heat the cooled steel to the two-phase critical annealing temperature of 800-850℃, keep it warm for 1 hour, and quench it to obtain low-alloy high-wear-resistant steel.
2. The low alloy high wear resistant steel according to claim 1, characterized in that: The alloy comprises the following chemical compositions in weight percentage: C 0.2%, Mn 1.2%, Si 0.5%, Cr 0.2%, Ni 0.2%, Cu 0.2%, Al 0.02%, Mo 0.2% and V 0.2%, with the balance being Fe.
3. The low alloy high wear resistant steel according to claim 1 or 2, characterized in that: The volume percentage of each phase in the low-alloy high-wear-resistant steel structure is: ferrite 15-25% and martensite 75-85%.
4. The low alloy high wear resistant steel according to claim 1, characterized in that: In step (2), the Ac3 temperature is 721°C.
5. The low alloy high wear resistant steel according to claim 1, characterized in that: In step (2), the normalizing temperature is 900°C and the acceleration rate is 20°C / s.
6. The low alloy high wear resistant steel according to claim 1, characterized in that: In step (2), the air cooling rate is 20°C / s.
7. The low alloy high wear resistant steel according to claim 1, characterized in that: In step (3), the critical annealing temperature of the two-phase region is 825°C.
8. The low alloy high wear resistant steel according to claim 1, characterized in that: In step (3), water quenching is used for quenching.
Citation Information
Patent Citations
Low-alloy wear-resistant steel and manufacturing method thereof
CN102676922A
Cited By
Lightweight wear-resistant composite needle cylinder for a compound needle circular weft knitting machine and a preparation method thereof
CN121344862B